Residential spatial differentiation at the community level in Hangzhou, China - Zhang, Ling; Wu, Baihong (International Journal of Strategic Property Management, 2023)
Residential spatial differentiation is an important social issue for every large city to explore. The “subcultural” clusters formed by the subjective choices of a city’s residents divide the living spaces of the city and create residential differentiation. A study of this phenomenon would help to facilitate the allocation of urban resources and the formulation of relevant development strategies. In recent years, Hangzhou, one of the major developed cities in China, has seen a gradual increase in the proportion of its non-local population. Employing principal component analysis and K-means clustering, this study investigated the city’s spatial differentiation of living spaces at the community level and identified the social clustering areas. The Shannon-Wiener index and the index of dissimilarity were used to examine the degree of residential segregation in each administrative district. The results showed that the functional distinctions among the districts of Hangzhou were pronounced and had certain degrees of class solidification. A certain spatial coupling was observed between residential differentiation and housing prices. More reasonable allocations of social resources would help to ameliorate the negative effects caused by the spatial differentiation of living spaces.